The Female Romantics : Nineteenth-century Women Novelists and Byronism. - Franklin, Caroline (Routledge studies in romanticism., 2012)
The nineteenth century is sometimes seen as a lacuna between two literary periods. In terms of women's writing, however, the era between the death of Mary Wollstonecraft and the 1860s feminist movement produced a coherent body of major works, impelled by an ongoing dialogue between Enlightenment 'feminism' and late Romanticism. This study focuses on the dynamic interaction between Lord Byron and Madame de Staël, Lady Morgan, Mary Shelley and Jane Austen, challenging previous critics' segregation of the male Romantic writers from their female peers. The Romantic movement in general unleashed th.